Community-Based Artificial Intelligence for Enhancing Productive Digital Literacy in Non-Formal Education: A Participatory Framework Study - Multazam, Multazam; Miftahudin, Ahmad; Qutni, Darul; Rimayati, Elfi; Isah, Musab (Journal of Nonformal Education, 2026)
BackgroundThe diffusion of artificial intelligence (AI) in education has expanded the opportunities for personalization and learning analytics. However, much of the discourse is still centered on formal education and commercial education technology, while non-formal education and lifelong learning in local communities have not received adequate attention.PurposeThis article aims to develop and analyze a Community-Based Artificial Intelligence (Community-Based AI/Cb-AI) framework that integrates the improvement of productive digital literacy for learners in non-formal educational institutions, especially Community Learning Activity Centers (PKBM) and Learning Activity Studios (SKB).MethodThis study uses a systematic literature study approach combined with conceptual framework analysis from two research tracks: (1) a community-based AI framework through participatory action research, and (2) a project-based learning model (PjBL) for increasing productive digital literacy in non-formal education settings.FindingsThe results of the study resulted in a Cb-AI-PjBL framework consisting of four pillars: (1) community-curated local knowledge repositories, (2) culturally responsive adaptive learning pathways, (3) multimodal access and digital literacy bridges, and (4) participatory governance and ethical oversight of AI. The integration of PjBL in this framework has proven to be effective in increasing productive digital literacy with an average increase of 25.4% in field trials.ConclusionThe Cb-AI-PjBL framework offers an alternative paradigm to the centralized education AI model by positioning the community as the owner of knowledge, the learner as the co-designer, and the AI as a tool that must be democratically managed. This framework is relevant to strengthen the role of PKBM and SKB as transformative spaces in Indonesia's non-formal education ecosystem.Novelty The novelty of this article lies in the development  of the integrated framework Cb-AI-PjBL (Community-Based AI for Productive Digital Literacy through Project-Based Learning) which for the first time combines the four pillars of community-based AI—local knowledge repositories, culturally responsive adaptive pathways, multimodal access, and participatory governance—with Project-Based Learning as a connecting pedagogical mechanism, specifically for the context of non-formal education (PKBM/SKB) in Indonesia.